PROTOTYPE OF 21st CENTURY ORIENTED COURSE CURRICULUM MODELS ON HIGH LEVEL BOTANY COURSE - Herliani - (PROSIDING SEMINAR KIMIA, 2015)
The curriculum is a set of plans and arrangements regarding the objectives, content and learning materials as well as a way of learning that is used as a guide to achieve certain courses. Learning the 21st century demand a change in the orientation of learning is to master the combination of content knowledge, skills, expertise, and proficiency. The 21st century requires the skills knowledge and understanding among all students. Learning and innovation skills of the 21st century is creativity and innovation, critical thinking and problem solving, communication, and collaboration.Content analysis Model Curriculum oriented courses conducted in the 21st Century: 1) National standards Universities which consists of competency standards, learning content standards, standards of learning and assessment standards of learning, 2) Indonesian National Qualifications Framework which consists of working ability, the ability of knowledge and ability manajereal, 3) Curriculum 2013, which consists of attitudes, knowledge and skills, 4) local wisdom consisting of local knowledge, local skills, and local sources, and 5) 21st century skills which consists of:a) science process skills (formulating the problem, formulating hypotheses, designing experiments, carry out experiments, collect and analyze data, draw conclusions, and communicate), b) thinking skills by using an evaluation tool taxonomy SOLO by classifying the level of ability of students at five levels, namely level prastruktural, unistruktural, multistruktural, rational and extended abstracs, and c) entrepreneurship with elements of self-employed; elements of knowledge, skills element and an element of vigilance.Analysis of the learning experience by using teaching strategies approach Science Process Skills, Problem Based Learning, Enquiry and Cooperative STAD.Products produced teaching Semester Lesson Plan (RPS), Instructional Materials, Student Activity Sheet (MFI) and the Assessment Sheet.The authority to develop or construct effective curriculum appropriate to the circumstances and needs of the region based on the National Education Standards in accordance with Permendikbud number 49 in 2014.